A Critique and Rethink of Modern Education in Africa ' s Development in the 21st Century - Babaci-Wilhite, Zehlia; Geo-JaJa, Macleans A. (Papers in Education and Development, 2018)
There has been an educational reform in Africa which has included the opening up of educational systems to market liberalisation. In this paper, we will illustrate the ways in which these reforms have been negative rather than positive for African education. The paper will critically analyse the reasons why the reforms have been inefficient. We will show how increasing social inequity and poverty are related to decreasing educational quality and increasing dropout rates. The African continent has the highest illiteracy rates in the world. The educational system is not contributing adequately to the development of Africa ' s human capabilities. Africa ' s knowledge has been omitted from the standard education curriculum. We claim that as long as local knowledge is not included, Africa will not develop on its own terms. We will conclude with some suggestions on ways in which to correct the problems created by market reforms and to move towards an education which is relevant to the social and developmental needs of Africa.